Self-assembled helical arrays for the stabilization of the triplet state - Nidhankar, Aakash D.; Goudappagouda; Kumari, Divya S. Mohana; Chaubey, Shailendra Kumar; Nayak, Rashmi; Gonnade, Rajesh G.; Kumar, G. V. Pavan; Krishnan, Retheesh; Babu, Sukumaran Santhosh (Angewandte Chemie-International Edition, 2020)
Room-temperature phosphorescence of metal and heavy atom-free organic molecules has emerged as an area of great potential in recent years. A rational design played a critical role in controlling the molecular ordering to impart efficient intersystem crossing and stabilize the triplet state to achieve room-temperature ultralong phosphorescence. However, in most cases, the strategies to strengthen phosphorescence efficiency have resulted in a reduced lifetime, and the available nearly degenerate singlet-triplet energy levels impart a natural competition between delayed fluorescence and phosphorescence, with the former one having the advantage. Herein, an organic helical assembly supports the exhibition of an ultralong phosphorescence lifetime. In contrary to other molecules, 3,6-phenylmethanone functionalized 9-hexylcarbazole exhibits a remarkable improvement in phosphorescence lifetime (>4.1 s) and quantum yield (11 %) owing to an efficient molecular packing in the crystal state. A right-handed helical molecular array act as a trap and exhibits triplet exciton migration to support the exceptionally longer phosphorescence lifetime.
Keywords: carbazole; helicity; phenylmethanone; ultralong phosphorescence; waveguiding

Total synthesis of (-)-2-methoxy-2-butenolide-3-cinnamate and its antimicrobial potentials - Said, Madhukar S.; Udavant, Rohini; Sahu, Amit Kumar; Khan, Abujunaid; Nayak, Rashmi; Dastager, Syed G.; Kumar, Pradeep; Gajbhiye, Jayant (Natural Product Research, 2020)
The first total synthesis of (-)-2-methoxy-2-butenolide-3-cinnamate (butenolide cinnamate) was achieved using commercially available starting material. The synthesized compound was found to have promising antibacterial activity against Gram-negative strainsEscherichia coli(ATCC 8739),Salmonella typhimurium(ATCC 23564) andPseudomonas aeruginosa(ATCC 19154) with a minimum inhibitory concentration of 2.0 mu g/mL, 1.0 mu g/mL and 2.0 mu g/mL, respectively. Notably, the compound was more potent against Gram-negative test strains than the Gram-positive test strains.
Keywords: antibacterial activity; butenolide cinnamate; Total synthesis

Tuning phosphorescence features of triphenylamines by varying functional groups and intermolecular interactions - Goudappagouda; Asokan, Kiran; Nayak, Rashmi; Krishnan, Retheesh; Babu, Sukumaran Santhosh (Dyes and Pigments, 2020)
Organic room temperature phosphorescent materials are known for their synthetic feasibility, tunable phosphorescence wavelength and lifetime, etc. Hence new design strategies have been applied on various fluorophores to improve phosphorescence features. Among those, triphenylamines are phosphorescence active due to the presence of nitrogen atom, propeller molecular structure, and intermolecular interactions in the crystal state. Here we have studied the room temperature phosphorescence of a series of triphenylamines with various functional groups. Detailed studies have shown that the phosphorescence can be fine-tuned by functional group modification. A long phosphorescence lifetime around 100 ms at room temperature in air can be achieved by the interplay of intermolecular interactions, singlet-triplet energy gap and extent of intersystem crossing using functional group variation. Interestingly, an exciplex assisted ultralong phosphorescence lifetime (more than 20 times) is observed for a combination of triphenylamine and naphthalenemonoimide in air.
Keywords: Exciplex; fluorescence; Phosphorescence; triphenylamine

Donor-acceptor based solvent-free organic liquid hybrids with exciplex emission and room temperature phosphorescence - Wakchaure, Vivek Chandrakant; Veer, Sairam D.; Nidhankar, Aakash D.; Goudappagouda; Nayak, Rashmi; Asokan, Kiran; Ravindranathan, Sapna; Babu, Sukumaran Santhosh (Chemical Communications, 2022)
Solvent-free organic liquids are well-known for their excellent luminescence features. Hence, the recent developments in this area have marked them as potential emitters with high quantum yield and enhanced processability. The support of an available liquid matrix enables doping to deliver hybrid liquids with intriguing luminescence features. In this direction, we report solvent-free liquid donor-acceptor pairs with exciplex emission and room temperature phosphorescence at very low acceptor loading. The underlying weak intermolecular interactions have been revealed by 2D NMR techniques and theoretical calculations. The formation of large-area thin films by exciplex and phosphorescent liquid hybrids will encourage the development of scalable lighting and display materials.